New findings on retinal microvascular changes in patients with primary COVID-19 infection: a longitudinal study - Zhang, Chenxi; Cheng, Shiyu; Chen, Huan; Yang, Jingyuan; Chen, Youxin (Frontiers in Immunology, 2024)
Purpose: To investigate the longitudinal alterations of retinal microvasculature in patients with primary coronavirus disease 2019 (COVID-19) infection. Methods:A cohort of participants who had never been infected with COVID-19 were recruited between December 2022 and May,2023 at Peking Union Medical College Hospital, in Beijing, China. Participants underwent comprehensive ophthalmologic examinations and fundus imaging, and follow-ups with the same imaging modality were conducted within one week and at two months post-recovery. Results:31 patients (61 eyes), with a mean age of 31.0±7.2 years old, were eligible for this study. All participants contracted mild COVID-19 infection within one month of baseline data collection. The average period for the first follow-up was 10.9±2.0 days and 61.0±3.5 days for the second follow-up. No clinical retinal microvasulopathy features were observed during the follow-ups. However, swept source-optical coherence tomography angiography analysis showed a significant increase in macular vessel density (MVD) from 60.76±2.88% at baseline to 61.59±3.72%(p=0.015) at the first follow-up, which subsequently returned to the baseline level of 60.23±3.33%(p=0.162) at the two-month post-recovery follow-up. The foveal avascular zone (FAZ) remained stable during the follow-ups with areas of 0.339±0.097mm2, 0.342±0.093mm2, and 0.344±0.098mm2 at the baseline, first follow-up (p=0.09) and second follow-up (p=0.052) , respectively. Central macular thickness, cube volume and ganglion cell-inner plexiform layer showed a transient decrease at the first follow-up(p＜0.001, p=0.039, p=0.002, respectively), and increased to baseline level at the two-month follow-up(p=0.401, p=0.368, p=0.438, respectively). Conclusions: Mild COVID-19 infection may temporarily and reversibly impact retinal microvasculature, characterized by a transient increase in retinal blood flow during the early recovery phase that returns to pre-infection level two months post-infection.